Application of software engineering to biomedicine - Ng, Clement Zheng Yang (2014)
The application of software engineering technique to biomedicine complements the biomedical process. Biological systems are extremely complex reactive systems that require a lot of analysis and comprehension. The use of formal methods can be beneficial for gaining new biological insights and experimental avenues. The model created could be analysed by model checking.